Chromosome spreading of the (TTAGGG)n repeats in the Pipa carvalhoi Miranda-Ribeiro, 1937 (Pipidae, Anura) karyotype - Zattera, Michelle Louise; Lima, Luana; Duarte, Iraine; Sousa, Deborah Yasmin de; Santos Araujo, Olivia Gabriela dos [UNESP]; Gazoni, Thiago [UNESP]; Mott, Tami; Recco-Pimentel, Shirlei Maria; Bruschi, Daniel Pacheco (Pensoft Publishers, 2019)
Pipidae is a clade of Anura that diverged relatively early from other frogs in the phylogeny of the group. Pipids have a unique combination of morphological features, some of which appear to represent a mix of adaptations to aquatic life and plesiomorphic characters of Anura. The present study describes the karyotype of Pipa carvalhoi Miranda-Ribeiro, 1937, including morphology, heterochromatin distribution, and location of the NOR site. The diploid number of P. carvalhoi is 2n=20, including three metacentric pairs (1, 4, 8), two submetacentric (2 and 7), three subtelocentric (3, 5, 6), and two telocentric pairs (9 and 10). C-banding detected centromeric blocks of heterochromatin in all chromosome pairs and the NOR detected in chromosome pair 9, as confirmed by FISH using the rDNA 28S probe. The telomeric probes indicated the presence of interstitial telomeric sequences (ITSs), primarily in the centromeric region of the chromosomes, frequently associated with heterochromatin, suggesting that these repeats are a significant component of this region. The findings of the present study provide important insights for the understanding of the mechanisms of chromosomal evolution in the genus Pipa, and the diversification of the Pipidae as a whole.
Keywords: Pipidae; chromosome banding; interstitial telomeric sequences; rearrangements; chromosome evolution